The concept of nation within de right wing discourse. An ideological analysis in the Chilean Congress debate. - Muñoz Navarro, Antonieta; Universidad de La Frontera (Pontificia Universidad Javeriana - Facultad de Comunicación y Lenguaje, 2008)
This is a politic communicational study about the Chilean senatorial discourse. We formulate that the traditional nation conceptual framework has a concretion as an ideology, and it is avoiding a democratic grow in the Republic of Chile because it is used, by the conservative sector, as the main argumentation against the main indigenous population in Chile: Mapuche people. We use the ideological discourse analysis to observe the conservative parliamentary debate referred to Mapuche people. This study reveals that the traditional nation principles are present on this discourse even in its pure form and it is continuously used against political aspirations of Mapuche people, which is frequently mixed with racism ideology. We finish by discussing about additional studies that would complement this and we generate some hypothetical political scenarios that, considering this political situation, would improve the democracy building process in Chile.